FORENSIC ANALYSIS OF PHISHING ATTACKS: INVESTIGATIVE APPROACH - Kainde, Quido Conferti; Tambanaung, Josua Setdefit; Inkiriwang, Valent Tio; Mile, Alexandra Anrala Putri (Informatika, Universitas Jenderal Soedirman, 2024)
Phishing attacks continue to pose a significant threat to cybersecurity, with perpetrators becoming increasingly sophisticated in crafting convincing fraudulent methods. This article examines the forensic analysis process used to effectively investigate phishing attacks. Through a review of existing literature, the author understands the workings of phishing and analyzes real cases that have occurred, followed by data collection using secondary sources. Using theories and insights gained from literature studies, the author analyzes and identifies important aspects of the conducted research data. A content analysis method is employed to analyze the data, determining the steps for prevention and investigation of phishing attacks. In this analysis, thematic and textual methods are applied to gather crucial components of a phishing attack. The analysis results indicate that forensic approaches and a deep understanding of phishing mechanisms can help protect data and significantly reduce the impact of phishing attacks. This article concludes by providing practical recommendations to enhance readiness in facing future phishing attacks.